Exploring the stability and dynamics of nanobubbles - Tan, Beng Hau (2017)
Nanoscale domains of gas in liquids, known as nanobubbles, have received substantial attention as much for their unusual fundamental properties as for their potential applications in microfluidics or cleaning. Due to the inability of the widely-used atomic force microscopy (AFM) to observe dynamic events, many basic properties of nanobubbles remain to be understood, such the strength of the line pinning that appears to facilitate their remarkable stability. Through experiments, theory and numerical simulations, we resolve some open questions in nanobubbles, with a particular focus on their dynamics and stability mechanisms. The first half of this thesis focuses on issues related to surface nanobubbles. To address an on-going problem with contamination, we demonstrate a method to distinguish between nanobubbles and polymeric drops of contamination by applying predominantly verticalor lateral forces on these objects. We make the first direct estimates of the line pinning on nanobubbles, through dynamic imaging with optical fluorescence microscopy. Since typical nucleation techniques are easily contaminated and lead to an uncontrollable distribution of nanobubbles, our results will be useful in developing techniques to control the distribution of nanobubbles for various applications. The second half of this thesis pertains to the observation of nanobubbles in an electron microscope. These nanobubbles appear not to be stabilised by the line pinning or oversaturation that sustain surface nanobubbles. We show instead that imaging conditions typical in a transmission electron microscope stabilises these nanobubbles by increasing the liquid's viscosity by orders of magnitude. Our results provide mechanistic understanding to the long-standing and puzzling observation that a wide range of phenomena in fluids imaged with electron microscopy appear to be significantly damped.